A systematic review examining the effectiveness of medicines information services for patients and the general public. (12th September 2019) - Williams, Matt; Jordan, Abbie; Scott, Jenny; Jones, Matthew D.
Abstract: Objectives: Hospital‐based patient medicines helpline services (PMHS) and medicines information services for the general public (MISGP) are available in many countries to support people with their medicines. Our aim was to examine the available evidence regarding the effectiveness of PMHS and MISGP. Methods: Searches were conducted using Medline, EMBASE, CINAHL, Scopus and Web of Science, on 11 August 2018. Forward and backward citation searches were conducted, grey literature was searched, and study quality/risk of bias was assessed. Findings were synthesised in a narrative synthesis. Where appropriate, weighted means were calculated. Key findings: Thirty‐two studies were identified for inclusion (17 published articles, 15 conference abstracts). Eighteen studies were conducted within the United Kingdom. Mean quality assessment was moderate (51%), and risk of bias was high (63%). PMHS and MISGP are both typically perceived as positive (e.g. 94% and 91% of participants were satisfied with using a PMHS and MISGP, respectively). For PMHS, the advice received is reported to be usually followed (94%, and 66% for MISGP). For both services, users report several positive outcomes (e.g. problems resolved/avoided, feeling reassured and improved health). PMHS may also be effective for correcting medicines‐related errors (up to 39% of calls may concern such errors) and for potentially avoiding medicines‐related harm (48% of enquiries concerned situations that were judged to have the potential to harm patients). Conclusions: Findings suggest that both PMHS and MISGP may be beneficial sources of medicines‐related support. However, the moderate quality and high risk of bias of studies highlight that more high‐quality research is needed.